PENGARUH HARGA, KEMASAN PRODUK DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN OLEH-OLEH KHAS PARIAMAN - Salfina, Lili (Menara Ilmu, 2017)
The purpose of this study is to determine the effect of price, product packaging and location to the purchase decision, either partially or simultaneously. Where the population in this study were consumers who bought Oleh-Oleh at Pusat Oleh-Oleh Khas Pariaman "ANE". While the sample taken as many as 100 respondents using Non-Probability Sampling technique and Accidental sampling approach. While the data processing in this study using SPSS version 16.0. Based on the result of research, the regression equation as follows. Y = 0.697 + 0.225 X1 + 0.368 X2 + 0.261 X3 + e. Price (X1) have a significant effect on purchasing decision with regression coefficient equal to 0,225. Product packaging (X2) has a significant effect on purchasing decisions with regression coefficient of 0.368, and location (X3) has a significant effect on purchasing decisions with regression coefficient of 0.261. Taken together, the product and location packaging have a significant effect on the purchase decision.Keywords: price, product packaging, location, purchase decision.